Oribatid mites (Acari, Sarcoptiformes) of Hormozgan province, southern Iran, with new records - Mohammad Ali Akrami; Zahra Eskandari-Nasab (Journal of Insect Biodiversity and Systematics)
This study was carried out to determine the fauna of oribatid mites (Oribatida) in Hormozgan province (southern Iran). Berlese funnel was used to obtain specimens from soil and leaf litter samples in various habitats in the province during the months of February to October 2021. Forty-three species belonging to 30 genera from 20 families of oribatid mites were collected from Bandar Abbas, Minab, Rudan and Hajiabad counties and identified. The species Javacarus (J.) porosus Hammer, 1979, Hoplophorella (H.) hamata (Ewing, 1909) and Lamellobates (L.) molecula molecula (Berlese, 1916) are recorded for the first time from Iran.